A Generic Language for Query and Viewtype Generation By-Example - Werner, Christopher; Wimmer, Manuel; Assmann, Uwe (2019 ACM/IEEE 22nd International Conference on Model Driven Engineering Languages and Systems Companion (MODELS-C), 2019)
In model-driven engineering, powerful query/view languages exist to compute result sets/views from underlying models. However, to use these languages effectively, one must understand the query/view language concepts as well as the underlying models and metamodels structures. Consequently, it is a challenge for domain experts to create queries/views due to the lack of knowledge about the computer-internal abstract representation of models and metamodels. To better support domain experts in the query/view creation, the goal of this paper is the presentation of a generic concept to specify queries/views on models without requiring deep knowledge on the realization of modeling languages. The proposed concept is agnostic to specific modeling languages and allows the query/view generation by-example with a simple mechanism for filtering model elements. Based on this generic concept, a generic query/view language is proposed that uses role-oriented modeling for its non-intrusive application for specific modeling languages. The proposed language is demonstrated based on the role-based single underlying model (RSUM) approach for AutomationML to create queries/views by-example, and subsequently, associated viewtypes to modify the result set or view.